Product compliance performance of Malaysian electrical and electronics manufacturing sector - Sabran, Muhamad Kamal (2012)
The study aims to investigate the quality improvement practices of Malaysian Electrical and Electronics manufacturers and differences may exist between them. Based on the findings, a proposed set of guidelines for Product Certification Scheme was established. Based on SIRIM QAS’s findings on compliance to product standard, the sampled manufacturers showed an increment in their failure rate. The gradual increment in the failure rate seems to indicate the alarming issue which concerns the manufacturers’quality practices. The objectives of this study is to investigate the influence of the quality improvement practices among Malaysian Electrical and Electronics manufacturers on their compliance performance. The differences between manufacturers were used as a guide to develop certification guidelines. A quantitative research method which involved the distribution of a set of questionnaire was used in the study. The findings have revealed that there tend to be a similar trend in the current quality improvement practice of the selected Electrical and Electronics manufacturers. ‘Process Management’ was selected to be the ‘most preferred’ quality improvement practice. ‘Process Control’ was the least preferred quality improvement practice. The relevant findings which furnished the details to complete the existing requirements were obtained by investigating the significant difference between the groups of manufacturers. From the findings, three aspects of quality improvement practice were found to be significantly different and they are Process Control (significant at alpha value 0.044), Customer Involvement (significant at alpha value 0.045) and Interfunctional Design Process (significant at alpha value 0.034). The present study’s findings were used to develop the Product Certification Guidelines for Product Certification Scheme. This guidelines will benefit local manufacturers to develop their procedure to comply with Product Certification Scheme especially to companies without ISO 9001 certified. This guidelines has pointed out all the three areas that manufacturer should pay attention to; quality system, product design, process control and quality control. Briefly, this guidelines is very useful for the manufacturer in order to satisfy regulatory requirements and customers expectation in terms of product quality and safety.